Performance of a pre‐procedural Mehran score to predict acute kidney injury after percutaneous coronary intervention. Issue 1 (9th September 2020) - Blanco, Anamarys; Rahim, Faisal; Nguyen, Michelle; Quach, Steven; Guduru, Sai; Makadia, Shraddha; Abusaada, Khalid
Abstract: Aim: Acute kidney injury (AKI) is a known complication of patients undergoing cardiac catheterization or percutaneous coronary interventions (PCI).The Mehran score was developed to identify patients at risk for AKI after cardiac catheterization or PCI, but its use of contrast volume as part of the score calculation limits its application prior to the procedure. In this study, we evaluated the utility of a modified Mehran score that utilizes only pre‐procedural data by excluding contrast volume. Methods: This was done in a retrospective fashion using data from patients who received PCI at our institution between July 2015 and December 2017 by evaluating the discriminative ability of the scoring systems for predicting outcomes through a receiver‐operator characteristic curve analysis. Results: One thousand five hundred and seven patients were included in the study. A total of 70 (4.6%) patients developed AKI. The removal of contrast volume from the Mehran score resulted in a small loss of discrimination with AUROC 0.73 vs 0.74, P = .01 for the pre‐procedural Mehran and the original Mehran, respectively. When compared to the original score, the pre‐procedural Mehran score had a four‐category net discrimination index (NRI) of ‑0.10 and an integrated discrimination index (IDI) for of −0.12. Conclusion: Despite a small loss in discrimination, there was no difference in the four‐category net discrimination index between the two scores. The pre‐procedural modified Mehran score is a useful clinical predictor of the risk of AKI in patients undergoing PCI. SUMMARY AT A GLANCE: This study evaluated a modified Mehran score utilizing pre‐procedural data excluding contrast volume. Retrospective data from 1507 patients undergoing percutaneous coronary interventions (PCI), 4.6% of whom developed AKI, was analysed. The removal of contrast volume from the Mehran score resulted in a small loss of discrimination. Therefore, pre‐procedural modified Mehran score is a useful clinical predictor of the risk of AKI in patients undergoing PCI.